OBJEK MATERIAL DAN OBJEK FORMAL ILMU MANAJEMEN PENDIDIKAN ISLAM - M. Ainur Rofiq; Kautsar Eka Wardhana; Yusnia Binti Kholifah (STKIP Subang, 2026)
This study aims to analyze the conceptualization of material and formal objects of Islamic educational management science within the contemporary epistemological framework. Employing a qualitative approach with intrinsic case study design, the research involved in-depth interviews with Islamic educational management experts, school/madrasah principals, and academics selected through purposive sampling. Data were analyzed using thematic analysis with trustworthiness criteria implementation to ensure findings credibility. Research findings reveal that material objects encompass all tangible and observable Islamic educational phenomena, including institutions, human resources, students, curriculum, and facilities integrated with Islamic values. Formal objects represent Islamic managerial perspectives integrating tawhid, khilafah, and accountability principles, providing transformative epistemological frameworks for Islamic educational management. The integration model of both objects produces holistic managerial approaches emphasizing not only operational efficiency but also character and spirituality formation. Model implementation requires transformational leadership capable of harmonizing technical and spiritual aspects throughout management stages. This research contributes to providing conceptual clarity regarding Islamic educational management scientific identity and offers practical guidance for curriculum development and quality Islamic educational institution management with strong character foundation.